FORMATION OF CREATIVE THINKING IN STUDENTS IN THE LEARNING PROCESS - Kholmatova Sh. M. (Bright Mind Publishing, 2025)
The article examines issues related to the formation of creative thinking in the learning process. The author describes methods for developing students’ creative abilities, considers the theory of inventive problem solving, and provides an example of a creative lesson.
Keywords: Creativity, creative tasks, development of creative abilities, creative thinking, creative lesson.